Household Impact of COVID-19 Pandemic in Development: Economic Perspective-A Review - Bekhzod Egamberdiev (Regional Science Inquiry, 2021)
In terms of the socio-economic crisis, the ravages of a pandemic shock indicate that people from developing countries are likely to be more vulnerable. The same direction of impact could be expected in the case of the COVID-19 pandemic; however, both scale and speed of this pandemic differ from others in the past. Therefore, we can expect causes to be different from those of past crises. Although emerging studies are available, the existing literature offers no systematic analysis of household vulnerability in the prism of development economics. Especially the interlinkages of causes and the relative importance of effects and coping strategies are not yet summarized. Therefore, this study aims to provide a systemic assessment of household effects of COVID-19 and tries to identify casual effects of the consequences, to which it adds policy recommendations. The systematic analysis undertaken in this study is based on a cluster analysis of 150 articles and reports provided in international literature. This study shows that two distinct impacts of the COVID-19 pandemic concern food security and market imbalance, together with socio-economic consequences, which a large number of studies identify as the core of a pandemic. Similarly, risk mitigation strategies such as strengthening farm support, food system resilience, and social protection need to be particularly promoted under COVID-19 conditions. The study also identifies research gaps especially in particularities of health outcomes in different food systems and on different economic development levels.
Keywords: Q10; Q11; Q13; Q18; 330; Food security; resilience; pandemic; income; poverty; inequality